Frustration, Excitement, Commitment: Preservice Teachers Reflect on their Fieldwork Experiences - Emily Arenz; Alexa Thornton (The University of Alabama, 2022)
The Purpose of Education: Engaging Active Minds, by Emily Arenz Understanding the Role of Teacher: Frustration to Dedication, by Alexa Thornton